Fifty years of urban accessibility: The impact of urban railway network on the land gradient in industrializing Berlin - Gabriel M. Ahlfeldt; Nicolai Wendland (ETH Zurich, KOF Swiss Economic Institute, 2008)
As the first to use an archival data set on historical land values of Berlin, Germany, from 1890 to 1936, we exploit exogenous variation in transport technology in order to test the validity of the monocentric city model. Endogenously determining the CBD, we conduct cross-section and time-difference analysis and model the land gradient in terms of straight-line distance and travel times. A counterfactual scenario indicates that a large proportion of urban decentralization is attributable to improvements in transport infrastructure. Controlling for spatial dependency, results suggest that the monocentric model fitted the city structure until the mid 20th century.
Keywords: N7; N9; R33; O12; 330; Transport Innovations; Land Values; Location Productivity; Economic History; Verkehrserschließung; Schienenpersonennahverkehr; Bodenpreis; Produktivität; Berlin (Region); Deutschland (bis 1945)